Manajemen Rekrutmen Dalam Meningkatan Kualitas Peserta Didik - Isman Isman (THE JOER: Journal Of Education Research, 2022)
Management is a function of achieving something through the activities of others and overseeing individual efforts to achieve common goals. The management functions are planning (Planning), organizing (organizing), directing (actuating), and controlling (controling). The focus of the research in this study is, 1) How is the recruitment strategy at SMPN 1 Plandaan Jombang, 2) How is the implementation of recruitment at SMPN 1 Plandaan Jombang, 3) What are the implications of implementing recruitment in improving the quality of students at SMPN 1 Plandaan Jombang. While the objectives of this study are 1) Analyzing recruitment strategies at SMPN I Plandaan Jombang, 2) Analyzing the implementation of recruitment at SMPN 1 Plandaan Jombang, 3) Analyzing the implications of implementing recruitment in improving the quality of students at SMPN 1 Plandaan Jombang. The type of research used is qualitative. (qualitative research) and the research approach is a case study. Then to determine the level of validity is the source of the data obtained from the provision of information by school principals, waka students, teachers, and education staff as well as documents of written materials. The results of this study are, 1) Recruitment Strategy for SMPN 1 Plandaan Jombang, namely: 1) CAR analysis, 2) Selection of applicant files, 3) Selection path, 4) School promotion, and 5) Re-registration. 2) Implementation of Recruitment at SMPN 1 Plandaan Jombang, namely: 1) Analysis of teaching load, 2) Coordination of committees, 3) Analysis of CAR burden, and 4) PPDB Portal. 3) Implications of Recruitment Implementation in Improving the Quality of Students at SMPN 1 Plandaan Jombang, namely: 1) Standard teaching load, 2) Registration path, and 3) Linearization of diplomas.